ESTIMATION OF INFANT MORTALITY RATES IN INDONESIA BY USING EMPIRICAL BEST LINEAR UNBIASED PREDICTION - Nadra Yudelsa Ratu; Easbi Ikhsan (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2021)
Infant Mortality Rate (IMR) is one of the many indicators that can measure the health status of a population in an area. IMR is also part of thethirdSustainable Development Goals (SDGs), namelyto ensure healthy lives and promote well-being for all of all ages. IMR was produced with direct estimation from the Indonesian Demographics Health Survey (IDHS). However, the result of the 2017 IDHS publicationindicated thatseveral direct estimationsof IMR in 34 provinces in Indonesia hadhigh relative standard error (RSE) values. Accurate data (from the RSE value) is neededfor policy making. Therefore, this paper focused onsmall area estimation (SAE) by using the empirical best linear unbiased prediction (EBLUP) method andestimatedIMR to the provincial level. SAE worksby using the strength of several variables from the village potential data (Potensi Desa) which correlates strongly with IMR. The results of the analysis with theRSEusedas a measure of model accuracy showed that by using the SAE EBLUP method in the IDHS data,an average RSE value of 15.23% was obtained, which is smaller than the direct estimate of theaverage RSE value of 29.51%. This research paper concludes that SAE using the EBLUP method is good for estimating the Provincial level IMR value in Indonesia in 2017.